Analysis of the Regulation of Renewable Energies in Peru - Mitma Ramírez, Riquel Ernes (2015)
This paper analyzes, from an auction design perspective, the results of the auction of renewable energy that the Peruvian State has initiated since 2008, allowing to show significant results such as the introduction of new technologies for power generation with low CO2 emissions, competitive prices and high levels of competition. Although they are also shown the outstanding issues as the lack of clear direction and heading for future of renewable energy, as well as the need to strengthen institutions to create areas of renewable energies to integrate synergies around the energy transition.